Physical characteristics and fibre diameter profile of Huacaya alpacas from La Raya Experimental Centre (Puno, Peru), according to age and sex - Quispe Coaquira, Jesús E. (2021)
The technological characteristics and the fibre diameter profile were determined according to age (1, 3, 5, 7 years) and sex (male, female) of Huacaya alpacas from the La Raya Experimental Centre (Puno, Peru). Fleece samples were taken from the middle rib at shearing and analysed with the OFDA 2000 equipment. The data were adjusted to multiple quadratic regression for the analysis of the exchange rates. The average diameter, comfort factor, curvature index and fibre length were statistically similar between sexes, while for age, the diameter increased (from 19.48 ± 0.25 to 24.82 ± 0.80 µm), and both the comfort factor (from 98.15 to 86.95%) and the fibre length (from 102.18 ± 12.92 to 75.00 ± 11.34 mm) decreased, while the curvature index shows no defined trend. The parameters that characterize the fibre diameter profile showed a single maximum value of the mean fibre diameter, which showed a concave curve with two ascending and descending segments. Exchange rates were positive and negative, although their magnitudes were small. It is concluded that the alpacas in the study present their own technological characteristics and the diameter profile configures a characteristic seasonal pattern coinciding with the rainfall seasonality of the Altiplano.